Analysis of Thermal Comfort in a Single-Family House in Poland - Krawczyk Natalia; Surmańska Sylwia (Civil and Environmental Engineering, 2020)
The article presents test research on thermal sensations, thermal preferences, as well as general thermal sensations in a single-family building. Graphs were drawn to determine the frequency of answers chosen by the respondents and the relationship between temperature and thermal sensations, as well as the influence of relative humidity on thermal sensations. A comparison was also made between the average thermal sensation vote and the PMV index, which determines the ‘predicted mean vote’ - estimated by the Fanger model. The aim of the study was to compare the actual feelings of the respondents with standard guidelines. As a result of this analysis it was found that the thermal sensations of the respondents do not comply with the adopted model included in the standard.